If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -4(2w + 1) = 6w + -4(6 + w) Reorder the terms: 20 + -4(1 + 2w) = 6w + -4(6 + w) 20 + (1 * -4 + 2w * -4) = 6w + -4(6 + w) 20 + (-4 + -8w) = 6w + -4(6 + w) Combine like terms: 20 + -4 = 16 16 + -8w = 6w + -4(6 + w) 16 + -8w = 6w + (6 * -4 + w * -4) 16 + -8w = 6w + (-24 + -4w) Reorder the terms: 16 + -8w = -24 + 6w + -4w Combine like terms: 6w + -4w = 2w 16 + -8w = -24 + 2w Solving 16 + -8w = -24 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. 16 + -8w + -2w = -24 + 2w + -2w Combine like terms: -8w + -2w = -10w 16 + -10w = -24 + 2w + -2w Combine like terms: 2w + -2w = 0 16 + -10w = -24 + 0 16 + -10w = -24 Add '-16' to each side of the equation. 16 + -16 + -10w = -24 + -16 Combine like terms: 16 + -16 = 0 0 + -10w = -24 + -16 -10w = -24 + -16 Combine like terms: -24 + -16 = -40 -10w = -40 Divide each side by '-10'. w = 4 Simplifying w = 4
| (-8y-5)(7y)y=-3 | | 8c-3d=6 | | 1d+8=2d-17 | | 0.7m+0.3m=2m-4 | | p=m+k+n | | -6(x-3)-4(6-6x)=12 | | -6-3(6+4x)=-24-2x | | 91=-7(2n-7) | | -5*(1/9+x)=0 | | 114=(x+2)15-3x | | -(4y+3z-4)= | | x+1(2)+x(2)=14 | | 2x+8=8+2x | | 18=c+5/2 | | (x+2)(x-1)(x+1)=0 | | -5a+2a=12-15 | | 15-2(2w+1)=7w-2(7+w) | | -187=2-7(4x+7) | | 9l=3m | | 5(-5-3p)=-8p+3 | | 7t-(t-4)=25 | | (4a-4)(4a-1)=0 | | 0.7n+4.7=5.4n | | 5a+2a=12-15 | | -7(-3m-8)=98 | | 10-3(4x-2)=5x | | 4x-9=2x+1 | | 10x-7=5(x+1) | | 4x-29.2=7.5x-6.8 | | 3g-21=20+2g | | 5n=20(4+0.25) | | (X+2)(x^2-1)=0 |